MISCOMMUNICATION IN INTER CULTURE INTERACTION IN SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVE - Suardana, I Ketut (Akademi Komunitas MAPINDO, 2018)
Bali is one of tourism objects visited by either domestic or international guests because Bali has been trusted to have uniqueness of culture, safety, cleanness and other reasons. Of course, in the process of interaction involving local people and guests (either domestic and international). Miscommunication often occurs in interpreting something during interaction process. One of the reasons is misunderstanding culture owned by the speaker and listener. Doing interaction language is involved in which culture is inside of language. To succeed communication, both speaker and listener must apply the concept of context of situation involving field, tenor and mode purposed by Halliday.This paper focuses on miscommunication caused by misunderstanding of application of context of situation in community. Halliday stated that whatever we spoke, listen, read and wrote was called text. This paper will analyze miscommunication from Systemic Functional Linguistics (SFL) specially context of situation. Therefore, the title of the paper is â€œMISCOMMUNICATION IN INTER CULTURE INTERACTION IN SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVEâ€. This paper analyzes some kinds of miscommunication which occurred in community. The result of research is that misinterpretation of text is caused by misunderstanding of cultureKeywords: field, tenor, mode, social interaction